American Rhinologic Society expert practice statement: Postoperative pain management and opioid use after sinonasal surgery. Issue 9 (11th July 2021) - Lee, Jivianne T.; Levine, Corinna G.; Overdevest, Jonathan B.; Higgins, Thomas S.; Manes, R. Peter; Myhill, Jeffrey A.; Soler, Zachary M.
Abstract : Summary: The goal of this American Rhinologic Society expert practice statement (EPS) is to provide clinically applicable, evidence‐based recommendations regarding pain management in sinonasal surgery. This EPS was developed following the recommended methodology and approval process as previously outlined. The topics of interest included preoperative counseling, local anesthesia, use of opioids for postoperative pain, use of nonopioid medication for postoperative pain, nonsteroidal anti‐inflammatory drugs and bleeding, and use of gabapentin for pain control. Following a modified Delphi approach, 6 statements were developed, 5 of which reached consensus and 1 that did not. These statements and accompanying evidence are summarized along with an assessment of future needs.